Preparation process of polyaluminum chloride
Through technical means such as batch feeding and synergistic agent addition, the preparation process of polymer aluminum chloride is optimized, and the problems of insufficient stability and poor low temperature adaptability in traditional processes are solved, and efficient, stable and environmentally friendly preparation of polymer aluminum chloride products is achieved.
Patent Information
- Application Number
- CN202510234388.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-28
AI Technical Summary
The traditional polymer aluminum chloride preparation process has problems such as insufficient stability, poor low temperature adaptability, high fluorine content, high energy consumption, environmental pollution problems and unbalanced product performance.
Technical measures such as batch feeding, precise control of reaction temperature and addition of synergistic agents are adopted to prepare polymer aluminum chloride products through polymerization, neutralization reaction, filtration and modulation, and the performance of solid products is improved through spray drying process optimization and addition of nano-silicon dioxide.
It significantly improves the coagulation effect and low temperature adaptability, improves the stability and solubility of the product, reduces fluorine content and energy consumption, reduces environmental pollution, expands the scope of application of the product, and reduces production costs.
Smart Images

Figure CN119954191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyaluminium chloride, and in particular to a preparation process of polyaluminium chloride. Background Art
[0002] Polyaluminium Chloride (PAC) is a highly efficient inorganic coagulant and is widely used in drinking water treatment, industrial wastewater treatment, municipal sewage treatment, papermaking industry, etc. Its main component is polynuclear hydroxyaluminum chloride, which forms a polynuclear structure with high charge density through complex reactions such as hydrolysis, polymerization, and addition, and has good flocculation performance and a wide pH adaptability range.
[0003] Traditional polyaluminium chloride preparation methods mainly include aluminium hydroxide method, aluminium ash method, calcium aluminate method, metallic aluminium method, etc. Among them, the aluminium hydroxide method is widely used due to its wide source of raw materials and relatively simple process. This method usually reacts aluminium hydroxide with hydrochloric acid at a certain temperature, and obtains polyaluminium chloride products through processes such as hydrolysis and polymerization. However, the aluminium hydroxide method in the prior art still has a series of problems to be solved: 1. Insufficient stability: Polyaluminium chloride products prepared by traditional processes are prone to continued polymerization during long-term storage, resulting in a decrease in effective ingredients and the formation of insoluble precipitates, which affects product quality and use effects.
[0004] 2. Poor adaptability to low temperatures: The coagulation effect of conventional products is significantly reduced under low temperature conditions (5-10°C), which limits their application in cold seasons or cold areas and cannot meet all-season and all-weather water treatment needs.
[0005] 3. High fluorine content: When using hydrochloric acid produced as a by-product of fluorine chemical enterprises as raw material, the residual fluorine content in the product is relatively high, which limits its application in the field of drinking water treatment and also causes serious corrosion to production equipment.
[0006] 4. High energy consumption: Especially in the preparation process of solid products, the traditional drying process has high energy consumption and low thermal efficiency, which increases production costs.
[0007] 5. Environmental pollution issues: If the acid mist, dust and other waste gases generated during the production process and the aluminum- and fluorine-containing wastewater are not handled properly, they will cause serious pollution to the environment.
[0008] 6. Unbalanced product performance: The traditional one-step production process makes it difficult to accurately control the reaction process, resulting in uneven distribution of aluminum polymers in the product and unstable coagulation effect.
[0009] With the increasingly stringent environmental protection requirements and the continuous advancement of water treatment technology, the market demand for efficient, stable and environmentally friendly polyaluminium chloride products is growing. Therefore, the development of a new polyaluminium chloride preparation process that can solve the above problems has important theoretical significance and practical value. Summary of the invention
[0010] The main purpose of the present invention is to provide a highly efficient, stable and environmentally friendly polyaluminium chloride preparation process in view of the problems existing in the prior art.
[0011] The object of the present invention is to provide a preparation process of polyaluminium chloride, comprising the following steps: (1) Polymerization reaction: 100.0-120.0 parts by weight of 31.0-33.0 wt % hydrochloric acid is added to a reaction kettle, stirring is started, 30.0-35.0 parts by weight of aluminum hydroxide is added in batches at a speed of 200-250 rpm under a slight negative pressure of -50 Pa to -100 Pa, heating is stopped after heating to 70±2° C., and the reaction is kept at 90-100° C. for 3.0-4.0 hours to obtain a first-step material; (2) Neutralization reaction: the first-stage material is transferred into a neutralization kettle, and under a slight negative pressure of -50 Pa to -100 Pa, the calcium aluminate powder is added in a ratio of 100.0 parts by weight of the first-stage material to 5.0-8.0 parts by weight of the calcium aluminate powder in 3-5 times, each time interval is 5-8 minutes, the stirring speed is 180-220 rpm, and the reaction is carried out at 85-95° C. for 0.5-0.8 hours; (3) filter pressing: adding 0.2-0.5 parts by weight of diatomaceous earth and 0.01-0.03 parts by weight of polyacrylamide to the material after the neutralization reaction, and then filter pressing at a pressure of 0.6-0.8 MPa to obtain a filtrate; (4) Modulation: The filtrate is cooled through a graphite heat exchanger, and the concentration is adjusted and corresponding additives are added according to the product type to obtain a polyaluminium chloride product.
[0012] Specifically, in step (1), the aluminum hydroxide is added in batches as follows: first add 20% of the total amount, react for 5-10 minutes, then add 30% of the total amount, and then react for 10-15 minutes before adding 50% of the total amount; the aluminum hydroxide content is ≥99.0% by weight, and the fineness is 100 mesh to 200 mesh.
[0013] Specifically, in step (2), 0.05-0.1 parts by weight of alkaline phosphate and 0.2-0.5 parts by weight of MgSO4·7H2O are further added; the calcium aluminate powder has a CaO·Al2O3 content of 65.0-75.0% by weight and a fineness of 200 mesh to 325 mesh.
[0014] Specifically, the modulation step further includes: (a) when preparing dilute polyaluminium chloride, the concentration of the filtrate is adjusted to 10.0±0.2 wt %, and 0.1-0.2 wt % of trisodium citrate, 0.05-0.1 wt % of modified polyacrylic acid and 0.01-0.02 wt % of MnCl2·4H2O are added; or (b) When preparing concentrated polyaluminium chloride, the concentration of the filtrate is adjusted to 12.5±0.3 wt %, and 0.1-0.2 parts by weight of a composite stabilizer is added.
[0015] Specifically, the process also includes a raw material pretreatment step: adding 0.1-0.2 parts by weight of H2O2 to the hydrochloric acid for pretreatment; in step (1), 0.1-0.3 parts by weight of FeCl3·6H2O are also added; in step (2), 0.2-0.4 parts by weight of Al2(SO4)3·18H2O are also added.
[0016] Specifically, the process also includes a waste gas treatment step: the waste gas generated in the process is discharged after being absorbed by two-stage water spraying and one-stage alkali solution spraying in sequence; wherein the pH value of the water spraying is 6-7 and 7-8 respectively, and the pH value of the alkali solution spraying is 10-11; the waste gas treatment uses a mixed filler of polypropylene ball rings and ceramic Raschig rings, with a filling density of 120-150kg / m³, a filler layer height of 1.2-1.5m / layer, and swirl plates and fillers are arranged alternately.
[0017] A preparation process of solid polyaluminium chloride comprises the following steps: (1) preparing concentrated polyaluminium chloride having a concentration of 12.5±0.3 wt % according to the method described; (2) Spray drying: preheat the concentrated polyaluminium chloride to 60-70°C, transport it to the spray drying buffer tank through a spray drying feed pump, and spray dry it under hot air at 320-350°C using a dual-fluid nozzle (gas-liquid ratio 2:1-3:1), with the outlet temperature controlled at 90-110°C and the negative pressure in the tower at -0.001 MPa, to obtain solid polyaluminium chloride; (3) Packaging: The solid polyaluminium chloride is transported to the packaging equipment via an auger conveyor for packaging, and the packaging specification is 25±0.2 kg / bag.
[0018] Specifically, in the step (2), 0.1-0.3 parts by weight of nano-silicon dioxide is added to the concentrated polyaluminium chloride as a fluidity improver; the Al2O3 content of the obtained solid polyaluminium chloride is ≥28.0% by weight, the insoluble matter content is ≤0.5% by weight, and the moisture content is ≤5.0% by weight.
[0019] Specifically, in step (3), a polyethylene plastic bag with a thickness of 0.08-0.10 mm is used as the inner layer, a polypropylene woven bag is used as the outer layer for packaging, and 3-5 g of desiccant is added into the packaging bag.
[0020] Specifically, the waste gas generated during the spray drying process is discharged through a 25m high exhaust stack after passing through a first-level cyclone dust removal, a first-level semi-finished product solution spray, a first-level water spray and a first-level alkali solution spray in sequence; the process also includes a recycling step: the hot gas (90-110°C) discharged from the spray drying is used to preheat the neutralization reaction feed, and the waste gas washing water is partially reused in the production of dilute polyaluminium chloride.
[0021] The beneficial effects of the present invention are: By adopting the polyaluminium chloride preparation process provided by the present invention, the following significant beneficial effects can be obtained: 1. Significantly improved coagulation effect: The present invention adopts technical measures such as batch feeding, precise control of reaction temperature and addition of synergist, so that the product has a more reasonable aluminum polymer distribution structure, and the turbidity removal rate is increased to 99.2-99.5%, which is 2-3 percentage points higher than traditional products; the floc formation speed is fast (1.0-1.8min), and the floc sedimentation speed is high (2.5-3.5cm / min), which greatly improves the water treatment efficiency.
[0022] 2. Greatly enhanced low temperature adaptability: By adding synergistic activators such as iron salts and manganese salts, the product of the present invention still maintains a removal rate of 98.6-99.0% at a low temperature of 5°C, and the efficiency retention rate reaches 99.2-99.7% at normal temperature, which is much higher than the 84.9-92.3% of traditional products, solving the problem of water treatment in winter.
[0023] 3. Product stability is significantly improved: through the optimization of neutralization reaction, addition of alkaline phosphate and composite stabilizer and other measures, the product of the present invention still maintains good stability after long-term storage (6 months), the Al2O3 content changes little (-0.5 to -1.0%), the coagulation effect retention rate is high (92.5-96.5%), the amount of sediment generated is small (1.0-1.8%), and the effective service life of the product is extended.
[0024] 4. The performance of the solid product is greatly improved: through optimization of the spray drying process, application of a dual-fluid nozzle, and addition of nano-silicon dioxide and other technical measures, the solid product of the present invention has excellent solubility (dissolution time 2.5-2.8min) and low insoluble matter content (0.25-0.35%), and low hygroscopicity (30-day moisture absorption rate is only 2.8-3.2%), which significantly improves the convenience of product use.
[0025] 5. Fluorine content is significantly reduced: through raw material pretreatment technology, especially adding calcium oxide for pre-precipitation, the fluorine content of the fluorine-free product of the present invention is reduced to 45ppm, which is much lower than the 1800ppm of traditional products, making the product more suitable for drinking water treatment. The residual fluorine content in the treated water meets the drinking water standard requirements.
[0026] 6. Significant resource and energy conservation: Through the comprehensive application of thermal energy cascade utilization, wastewater recycling and efficient waste gas treatment system, the wastewater generation of the process of the present invention is reduced by 33-40%, the waste gas treatment efficiency is increased by 7.5-14.8 percentage points, and the COD and fluoride emissions are reduced by 58-86% and 93-96% respectively, which greatly reduces the production cost and environmental impact.
[0027] 7. Wider scope of application: By adjusting the process parameters and the ratio of additives, the present invention can prepare different products such as dilute polyaluminium chloride (10%), concentrated polyaluminium chloride (12.5%) and solid polyaluminium chloride (≥28%) according to needs, meeting the needs of different application scenarios from urban drinking water treatment to industrial wastewater treatment.
[0028] 8. Significant economic benefits: The process of the present invention makes full use of the by-product hydrochloric acid of fluorine chemical enterprises to convert waste into valuable products, which not only reduces the cost of raw materials but also reduces the environmental burden; at the same time, the improvement of product performance reduces the dosage in actual application by 10-20%, further reducing the user's cost of use.
[0029] In summary, the present invention successfully solves the deficiencies of the traditional polyaluminium chloride production process in terms of product performance, stability, adaptability, environmental protection, etc. through the comprehensive application of a series of innovative technical measures, has significant technological advancement and practical value, and provides an efficient, stable and environmentally friendly polyaluminium chloride preparation process for the water treatment field. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the production process of dilute polyaluminium chloride of the present invention; Figure 2 The present invention is a schematic diagram of the production process of concentrated polyaluminium chloride and solid aluminium chloride. DETAILED DESCRIPTION
[0031] This embodiment provides a preparation process of dilute polyaluminium chloride, which adopts a two-step preparation method and obtains a product with good stability and excellent coagulation effect by precisely controlling the reaction conditions.
[0032] Specifically, the preparation process of this embodiment includes the following steps: (1) Polymerization reaction: First, 100.0 parts by weight of 31.0% by weight hydrochloric acid was added to the reactor, stirring was started, and the speed was adjusted to 200 rpm. Under a slight negative pressure of -50 Pa, 30.0 parts by weight of aluminum hydroxide (content 99.0% by weight, fineness 150 μm) was added in batches, of which 20% (6.0 parts by weight) of the total amount was added first, and 30% (9.0 parts by weight) of the total amount was added after 5 minutes of reaction, and 50% (15.0 parts by weight) of the total amount was added after 10 minutes of reaction. Then, the heating was stopped after indirect heating to 70°C by steam, and the temperature was naturally raised to 90°C by using the heat of reaction, and the reaction was kept at this temperature for 3.0 hours to obtain a first-step material.
[0033] In this step, adding aluminum hydroxide in batches can effectively control the reaction exothermic rate and avoid drastic temperature fluctuations, thereby increasing the complexation degree of aluminum ions. Preferably, an appropriate stirring speed is maintained during the reaction to ensure that the reaction proceeds evenly while avoiding excessive bubbles caused by too fast stirring.
[0034] (2) Neutralization reaction: All the first-stage materials were transferred to a neutralization kettle. Under a slight negative pressure of -60 Pa, 100.0 parts by weight of the first-stage materials and 5.0 parts by weight of calcium aluminate powder (CaO·Al2O3 content 70.0% by weight, fineness 200 mesh) were added in three portions, with an interval of 6 minutes between each addition. At the same time, 0.05 parts by weight of alkaline phosphate (Na3PO4) and 0.2 parts by weight of MgSO4·7H2O were added. The stirring speed was adjusted to 180 rpm, and the reaction was carried out at 85°C for 0.5 hours.
[0035] The alkaline phosphate added in this step can promote the formation of Al-OH-Cl bonds and improve product stability, while magnesium sulfate forms a synergistic complex structure with calcium aluminate to further enhance product stability.
[0036] (3) Filtration: Add 0.2 parts by weight of diatomaceous earth and 0.01 parts by weight of polyacrylamide to the material after the neutralization reaction, mix thoroughly, and then send it into a plate and frame filter press for filtration at a pressure of 0.6 MPa to obtain a filtrate.
[0037] Using diatomaceous earth as a filter aid can significantly improve filtration performance, reduce the water content of the filter cake, and increase filtration efficiency. Adding an appropriate amount of polyacrylamide can further enhance the flocculation effect and make the filtrate clearer.
[0038] (4) Modulation: The filtrate is cooled to 30°C through a graphite heat exchanger, and according to the Baume determination result, an appropriate amount of softened water is added to adjust the concentration to 10.0 wt% (Al2O3 content). Then, 0.1 wt% of trisodium citrate, 0.05 wt% of modified polyacrylic acid and 0.01 wt% of MnCl2·4H2O are added, and the final dilute polyaluminium chloride product is obtained after thorough mixing.
[0039] The trisodium citrate added in this step acts as a stabilizer to effectively prevent the hydrolysis of aluminum salt; the modified polyacrylic acid acts as an anti-settling agent to improve the storage stability of the product; and a small amount of manganese salt acts as an activator to significantly improve the coagulation effect of the product.
[0040] (5) Waste gas treatment: The waste gas generated during the entire production process is sequentially absorbed by two-stage water spraying (pH values are 6 and 7 respectively) and one-stage 10% NaOH alkaline solution spraying (pH value is 10), and then discharged through a 20m high exhaust pipe. The waste gas treatment system uses a mixed filler of polypropylene ball rings and ceramic Raschig rings with a filling density of 120kg / m³. The height of each layer of filler is 1.2m, and the swirl plates and fillers are arranged alternately, which greatly improves the gas-liquid contact efficiency.
[0041] The finally obtained dilute polyaluminium chloride product has the following characteristics: Al2O3 content 10.0% by weight, alkalinity 35%, pH value (1% solution) 3.8, relative density (20°C) 1.22, and turbidity ≤10NTU.
[0042] This embodiment provides a preparation process of concentrated polyaluminium chloride, and a high-concentration and high-stability product is obtained by optimizing reaction parameters and adding synergists.
[0043] Specifically, the preparation process of this embodiment includes the following steps: (1) Raw material pretreatment: Take 120.0 parts by weight of 33.0 wt% hydrochloric acid, add 0.2 parts by weight of H2O2 (based on the weight of hydrochloric acid), stir evenly, and let stand for 1 hour to fully oxidize Fe²⁺ to Fe³⁺, so as to improve the color stability of the product.
[0044] (2) Polymerization reaction: Add the pretreated hydrochloric acid into the reactor, start stirring, and adjust the speed to 250 rpm. Under a slight negative pressure of -80 Pa, add 35.0 parts by weight of aluminum hydroxide (content 99.5% by weight, fineness 120 μm) in batches, and add 0.3 parts by weight of FeCl3·6H2O as a synergistic flocculation factor. After heating to 70°C, stop heating, use the reaction heat to naturally raise the temperature to 100°C, keep the temperature for 4.0 hours, and obtain the first-step material.
[0045] In this step, adding an appropriate amount of ferric chloride can serve as a synergistic flocculation factor to form a composite flocculation system with aluminum ions, which significantly improves the coagulation performance of the product, especially for low-temperature water treatment.
[0046] (3) Neutralization reaction: All the first-stage materials were transferred to the neutralization kettle. Under a slight negative pressure of -100 Pa, 100.0 parts by weight of the first-stage materials and 8.0 parts by weight of calcium aluminate powder (CaO·Al2O3 content 75.0% by weight, fineness 325 mesh) were added in 5 times, with an interval of 8 minutes between each addition. At the same time, 0.1 parts by weight of alkaline phosphate (Na3PO4), 0.5 parts by weight of MgSO4·7H2O and 0.4 parts by weight of Al2(SO4)3·18H2O were added as structural regulators. The stirring speed was adjusted to 220 rpm and the reaction was carried out at 95°C for 0.8 hours.
[0047] The aluminum sulfate added in this step acts as a structural regulator, which can adjust the polymerization degree distribution of the product, optimize the coagulation performance and stability of the product, and effectively prevent turbidity and precipitation of the product under high concentration conditions.
[0048] (4) Filtration: Add 0.5 parts by weight of diatomaceous earth and 0.03 parts by weight of polyacrylamide to the material after the neutralization reaction, mix thoroughly, and then send it into a plate and frame filter press for filtration at a pressure of 0.8 MPa to obtain a filtrate.
[0049] (5) Modulation: The filtrate is cooled to 35°C through a graphite heat exchanger, and the concentration is adjusted to 12.5 wt% (Al2O3 content) according to the Baume determination result, and 0.2 parts by weight of a composite stabilizer (a mixture of phosphate and polymer) is added, and the mixture is fully mixed to obtain the final concentrated polyaluminium chloride product.
[0050] The composite stabilizer added in this step can effectively prevent aluminum salt hydrolysis and polymer degradation under high concentration conditions, extend the shelf life of the product, and maintain stable coagulation performance.
[0051] The concentrated polyaluminium chloride product obtained has the following characteristics: Al2O3 content 12.5% by weight, alkalinity 45%, pH value (1% solution) 4.0, relative density (20°C) 1.32, and a stable period of ≥6 months (at room temperature).
[0052] This embodiment provides a preparation process of solid polyaluminium chloride, and a solid product with good fluidity and excellent solubility is obtained by optimizing spray drying parameters and adding a fluidity improver.
[0053] Specifically, the preparation process of this embodiment includes the following steps: (1) Preparation of concentrated polyaluminium chloride: Concentrated polyaluminium chloride with a concentration of 12.5 wt % was prepared according to the method of Example 2.
[0054] (2) Spray drying: The concentrated polyaluminium chloride is preheated to 65°C, and 0.2 parts by weight of nano-silicon dioxide is added as a fluidity improver, and then transported to the spray drying buffer tank through a spray drying feed pump. Spray drying is performed using a two-fluid nozzle (gas-liquid ratio 2.5:1) under hot air at 340°C, the outlet temperature is controlled at 100°C, and the negative pressure in the tower is -0.001MPa, to obtain solid polyaluminium chloride powder.
[0055] In this step, adding nano silicon dioxide as a fluidity improver can significantly improve the fluidity of the solid product, prevent agglomeration, and improve the solubility of the product. Preferably, by controlling the inlet and outlet temperatures of the spray drying, the product can be prevented from being overly pyrolyzed while ensuring sufficient evaporation of water, thereby maintaining the activity of the product.
[0056] (3) Packaging: The solid polyaluminium chloride powder is transported to the packaging equipment via an auger conveyor and packaged in a polyethylene plastic bag with a thickness of 0.10 mm as the inner layer and a polypropylene woven bag as the outer layer. The net weight of each bag is 25 kg, and 5 g of desiccant is added to the packaging bag to prevent the product from absorbing moisture and agglomerating.
[0057] (4) Waste gas treatment: The waste gas generated during the spray drying process is discharged through a 25m high exhaust pipe after passing through a first-stage cyclone dust removal, a first-stage semi-finished product solution spray, a first-stage water spray (pH value 8) and a first-stage 10% NaOH alkali solution spray (pH value 11). At the same time, the hot gas (100°C) discharged from the spray drying is used to preheat the neutralization reaction feed to achieve energy recovery.
[0058] The obtained solid polyaluminium chloride product has the following characteristics: Al2O3 content 30.0% by weight, insoluble matter content 0.3% by weight, moisture content 3.5% by weight, particle size distribution 95% passing through 80 mesh sieve, dissolution time ≤ 3 minutes (in 25°C water).
[0059] This embodiment provides a preparation process of low-aluminum and high-efficiency dilute polyaluminium chloride. By adjusting the ratio of aluminium salt to auxiliary agent and adding an activity enhancer, a product with low aluminium content but excellent coagulation effect is obtained.
[0060] Specifically, the preparation process of this embodiment includes the following steps: (1) Polymerization reaction: 110.0 parts by weight of 31.5% hydrochloric acid was added to the reactor, stirring was started, and the speed was adjusted to 220 rpm. Under a slight negative pressure of -70 Pa, 32.0 parts by weight of aluminum hydroxide (content 99.2% by weight, fineness 180 μm) were added in batches, of which 20% of the total amount was added first, 30% of the total amount was added after 8 minutes of reaction, and 50% of the total amount was added after 12 minutes of reaction. At the same time, 0.2 parts by weight of FeCl3·6H2O and 0.01 parts by weight of MnCl2·4H2O were added as synergistic activators. After the temperature was raised to 70°C, heating was stopped, and the temperature was naturally raised to 95°C by using the heat of reaction, and the reaction was kept warm for 3.5 hours to obtain a first-step material.
[0061] In this step, iron salt and manganese salt are added simultaneously as synergistic activators, which can produce a significant synergistic effect and maintain excellent coagulation effect under conditions of lower aluminum content. It is particularly suitable for treating low turbidity and low temperature water quality.
[0062] (2) Neutralization reaction: All the first-stage materials were transferred to a neutralization kettle. Under a slight negative pressure of -80 Pa, 100.0 parts by weight of the first-stage materials and 6.5 parts by weight of calcium aluminate powder (CaO·Al2O3 content 68.0% by weight, fineness 250 mesh) were added in 4 portions, with an interval of 7 minutes between each addition. At the same time, 0.08 parts by weight of alkaline phosphate (Na3PO4), 0.3 parts by weight of MgSO4·7H2O and 0.3 parts by weight of Al2(SO4)3·18H2O were added. The stirring speed was adjusted to 200 rpm, and the reaction was carried out at 90°C for 0.6 hours.
[0063] (3) Filtration: 0.4 parts by weight of diatomaceous earth and 0.02 parts by weight of polyacrylamide were added to the material after the neutralization reaction, and after being fully mixed, the mixture was sent to a plate and frame filter press and filtered at a pressure of 0.7 MPa to obtain a filtrate.
[0064] (4) Preparation: The filtrate was cooled to 32°C by a graphite heat exchanger and the concentration was adjusted to 9.0 wt% (Al2O3 content). Then, 0.15 wt% of trisodium citrate, 0.08 wt% of modified polyacrylic acid, 0.015 wt% of MnCl2·4H2O, 0.01 wt% of CuSO4·5H2O and 0.01 wt% of ZnCl2 were added and mixed thoroughly to obtain the final product.
[0065] In this step, copper salt and zinc salt are added as activity enhancers, which can further improve the coagulation activity of the product, so that even a lower concentration of polyaluminium chloride can obtain an excellent coagulation effect, while reducing product costs and environmental impact.
[0066] (5) Waste gas treatment: The waste gas was treated according to the method of Example 1.
[0067] The obtained low-aluminum high-efficiency polyaluminium chloride product has the following characteristics: Al2O3 content 9.0% by weight, alkalinity 40%, pH value (1% solution) 4.2, relative density (20°C) 1.20, and coagulation effect equivalent to conventional 10.0% by weight product.
[0068] This embodiment provides a preparation process of high-basicity concentrated polyaluminium chloride. By adjusting the process parameters and the ratio of additives, a high-basicity and high-stability product is obtained, which is particularly suitable for high-turbidity water treatment.
[0069] Specifically, the preparation process of this embodiment includes the following steps: (1) Raw material pretreatment: Take 115.0 parts by weight of 32.0 wt % hydrochloric acid, add 0.15 parts by weight of H2O2, stir evenly, and let stand for 1.5 hours for pretreatment.
[0070] (2) Polymerization reaction: Add the pretreated hydrochloric acid into the reactor, start stirring, and adjust the speed to 230 rpm. Under a slight negative pressure of -60 Pa, add 33.0 parts by weight of aluminum hydroxide (content 99.3% by weight, fineness 130 μm) in batches, and add 0.15 parts by weight of FeCl3·6H2O at the same time. After the temperature rises to 70°C, stop heating, and use the reaction heat to naturally rise to 92°C. Keep the temperature for 3.2 hours to obtain the first-step material.
[0071] (3) Neutralization reaction: All the first-stage materials were transferred to the neutralization kettle. Under a slight negative pressure of -90Pa, 100.0 parts by weight of the first-stage materials and 7.0 parts by weight of calcium aluminate powder (CaO·Al2O3 content 72.0% by weight, fineness 280 mesh) were added in 4 portions, with an interval of 7 minutes between each addition. At the same time, 0.07 parts by weight of alkaline phosphate, 0.4 parts by weight of MgSO4·7H2O, 0.2 parts by weight of Al2(SO4)3·18H2O and 0.1 parts by weight of Na2CO3 were added as alkalinity regulators. The stirring speed was adjusted to 210 rpm, and the reaction was carried out at 92°C for 0.7 hours.
[0072] In this step, adding a small amount of sodium carbonate as an alkalinity regulator can increase the alkalinity of the product, enhance the treatment effect on high turbidity water, and maintain the stability of the product.
[0073] (4) Filtration: 0.3 parts by weight of diatomaceous earth and 0.025 parts by weight of polyacrylamide were added to the material after the neutralization reaction, and after thorough mixing, the mixture was sent to a plate and frame filter press for filtration at a pressure of 0.75 MPa to obtain a filtrate.
[0074] (5) Modulation: The filtrate was cooled to 33° C. through a graphite heat exchanger, the concentration was adjusted to 11.0 wt % (Al 2 O 3 content), and 0.15 parts by weight of a composite stabilizer was added and mixed thoroughly to obtain the final product.
[0075] The high basicity polyaluminium chloride product of this embodiment has the following characteristics: Al2O3 content 11.0% by weight, basicity 65%, pH value (1% solution) 4.5, relative density (20°C) 1.26, and is particularly suitable for treating raw water with high turbidity and high organic matter content.
[0076] This embodiment provides a preparation process of fluorine-free solid polyaluminium chloride, performs deep treatment on fluorine-containing hydrochloric acid, optimizes the spray drying process, and obtains a solid product with extremely low fluorine content.
[0077] Specifically, the preparation process of this embodiment includes the following steps: (1) Deep treatment of raw materials: 120.0 parts by weight of 33.0% by weight hydrochloric acid (fluorine content: 2500 ppm) was added with 0.2 parts by weight of H2O2 and 1.0 parts by weight of CaO. The mixture was stirred for 2 hours and then allowed to stand for 12 hours. The supernatant was filtered through a filter cloth to obtain pretreated hydrochloric acid in which the fluorine content was reduced to below 200 ppm.
[0078] In this step, the addition of calcium oxide can react with the fluoride ions in the hydrochloric acid to generate insoluble CaF2 precipitates, significantly reducing the fluorine content in the hydrochloric acid and laying the foundation for the preparation of fluorine-free products.
[0079] (2) Polymerization reaction: Add the pretreated hydrochloric acid into the reactor, start stirring, and adjust the speed to 240 rpm. Under a slight negative pressure of -75 Pa, add 34.0 parts by weight of aluminum hydroxide and 0.25 parts by weight of FeCl3·6H2O in batches. After the temperature rises to 70°C, stop heating, and use the reaction heat to naturally rise to 98°C. Keep the temperature for 3.8 hours to obtain the first-step material.
[0080] (3) Neutralization reaction: All the first-stage materials were transferred to the neutralization kettle. Under a slight negative pressure of -95 Pa, the calcium aluminate powder was added in 5 times according to the ratio of 100.0 parts by weight of the first-stage materials to 7.5 parts by weight of calcium aluminate powder, with an interval of 6 minutes between each addition. At the same time, 0.09 parts by weight of alkaline phosphate, 0.45 parts by weight of MgSO4·7H2O and 0.35 parts by weight of Al2(SO4)3·18H2O were added. The stirring speed was adjusted to 215 rpm, and the reaction was carried out at 93°C for 0.75 hours.
[0081] (4) Filtration: 0.45 parts by weight of diatomaceous earth and 0.025 parts by weight of polyacrylamide were added to the material after the neutralization reaction, and after thorough mixing, the mixture was sent to a plate and frame filter press for filtration at a pressure of 0.75 MPa to obtain a filtrate.
[0082] (5) Spray drying: The filtrate was adjusted to a concentration of 12.5 wt% and then preheated to 68°C, 0.25 parts by weight of nano-silicon dioxide was added, and the mixture was transported to a spray drying buffer tank through a spray drying feed pump. Spray drying was performed using a two-fluid nozzle (gas-liquid ratio 3:1) under hot air at 335°C, the outlet temperature was controlled at 105°C, and the negative pressure in the tower was -0.001 MPa to obtain solid polyaluminium chloride powder.
[0083] In this step, a higher gas-liquid ratio and an appropriate outlet temperature are used, which is conducive to obtaining a product with uniform particle size, low water content and good solubility, while minimizing the residual fluorine in the product.
[0084] (6) Packaging: The solid polyaluminium chloride powder is transported to the packaging equipment by an auger conveyor and packaged in a polyethylene plastic bag with a thickness of 0.09 mm as the inner layer and a polypropylene woven bag as the outer layer. The net weight of each bag is 25 kg, and 4 g of desiccant is added to the packaging bag.
[0085] (7) Waste gas treatment and energy recovery: Waste gas treatment and energy recovery are performed according to the method of Example 3.
[0086] The obtained fluorine-free solid polyaluminium chloride product has the following characteristics: Al2O3 content 29.5% by weight, fluorine content ≤50ppm, insoluble matter content 0.4% by weight, moisture content 4.0% by weight, and is particularly suitable for drinking water treatment and food industry water treatment.
[0087] Through the detailed description of the above embodiments, various implementation methods of the polyaluminium chloride preparation process of the present invention are fully demonstrated, covering the preparation methods of different types of products and the optimization combination of various process parameters. The technical scheme of the present invention solves the problems of poor stability, unsatisfactory coagulation effect, narrow environmental adaptability, etc. of traditional polyaluminium chloride products by accurately controlling the reaction conditions, adding a variety of synergistic additives, optimizing the process flow, etc., and obtains a series of products with excellent performance and wide application range.
[0088] This comparative example adopts the traditional single-step method to prepare dilute polyaluminium chloride, and does not use the technical measures of the present invention such as step-by-step feeding and synergistic additives.
[0089] Specifically, the preparation process of Comparative Example 1 includes the following steps: (1) Reaction: 100.0 parts by weight of 31.0% by weight hydrochloric acid was added to a reaction kettle, stirring was started, and the speed was adjusted to 150 rpm. 30.0 parts by weight of aluminum hydroxide was added at once under normal pressure, and then heated to 90° C. and kept warm for 4.0 hours to obtain a reactant.
[0090] (2) Filtration: The reactants are directly sent to a plate and frame filter press and filtered at a pressure of 0.5 MPa to obtain a filtrate.
[0091] (3) Modulation: The filtrate was cooled to room temperature and the concentration was adjusted to 10.0 wt % (Al2O3 content) to obtain the final product.
[0092] The obtained polyaluminium chloride product has the following characteristics: Al2O3 content 10.0% by weight, alkalinity 25%, pH value (1% solution) 3.2, relative density (20°C) 1.22, and turbidity 15NTU.
[0093] Compared with Example 1, the coagulation effect of the product prepared in Comparative Example 1 is poor, especially under low temperature conditions, the coagulation efficiency decreases by more than 50%; the product stability is poor, and obvious precipitation occurs after storage for more than 3 months; more dosage is required during use to achieve the same treatment effect, which increases the cost of use.
[0094] This comparative example omits the neutralization reaction step, and directly proceeds from the polymerization reaction to the filter pressing modulation, without adding synergists such as calcium aluminate powder and alkaline phosphate.
[0095] Specifically, the preparation process of Comparative Example 2 includes the following steps: (1) Polymerization reaction: 120.0 parts by weight of 33.0% by weight hydrochloric acid was added to a reactor, stirring was started, and the speed was adjusted to 200 rpm. 35.0 parts by weight of aluminum hydroxide was added twice under normal pressure. The temperature was raised to 100° C. and the reaction was carried out at this temperature for 5.0 hours to obtain a reactant.
[0096] (2) Filtration: The reactants are directly sent to a plate and frame filter press and filtered at a pressure of 0.6 MPa to obtain a filtrate.
[0097] (3) Modulation: The filtrate was cooled to room temperature and the concentration was adjusted to 12.5 wt % (Al2O3 content) to obtain the final product.
[0098] The concentrated polyaluminium chloride product obtained has the following characteristics: Al2O3 content 12.5% by weight, alkalinity 20%, pH value (1% solution) 2.8, relative density (20°C) 1.32, and a stable period of about 2 months (at room temperature).
[0099] Compared with Example 2, the product prepared in Comparative Example 2 has low alkalinity and poor coagulation effect, especially the treatment effect on high turbidity water is not ideal; the product has poor stability and will show stratification and crystallization during long-term storage; the product is highly acidic and more corrosive to equipment.
[0100] This comparative example adopts conventional hot air drying instead of spray drying to prepare solid polyaluminium chloride, and does not adopt flowability improver and precise temperature control.
[0101] Specifically, the preparation process of Comparative Example 3 includes the following steps: (1) Preparation of concentrated polyaluminium chloride: Concentrated polyaluminium chloride with a concentration of 12.5 wt % was prepared according to the method of Comparative Example 2.
[0102] (2) Hot air drying: Pour the concentrated polyaluminium chloride directly into a drying tray and place it in a hot air circulation oven at 150°C for 24 hours to obtain a solid product.
[0103] (3) Crushing and packaging: The dried block product is crushed with a crusher, sieved and then packaged.
[0104] The obtained solid polyaluminium chloride product has the following characteristics: Al2O3 content 28.0% by weight, insoluble matter content 1.2% by weight, water content 8.5% by weight, and dissolution time of about 10 minutes (in 25°C water).
[0105] Compared with Example 3, the product prepared in Comparative Example 3 has uneven particle size, poor solubility, and is prone to caking and insoluble matter during use; the product has strong hygroscopicity and is prone to caking during storage; the solution is turbid after dissolution and contains a large amount of insoluble matter, which affects the use effect.
[0106] In this comparative example, no synergistic activators such as iron salts and manganese salts were added during the preparation of low-aluminum polyaluminium chloride.
[0107] Specifically, the preparation process of Comparative Example 4 includes the following steps: (1) Polymerization reaction: 110.0 parts by weight of 31.5% by weight hydrochloric acid was added to a reactor, stirring was started, and the speed was adjusted to 200 rpm. 32.0 parts by weight of aluminum hydroxide was added at once. The temperature was raised to 95° C. and the reaction was carried out at this temperature for 4.0 hours to obtain a reactant.
[0108] (2) Neutralization reaction: The reactants were transferred to a neutralization kettle, 6.5 parts by weight of calcium aluminate powder was added, and the mixture was reacted at 90° C. for 1.0 hour.
[0109] (3) Filtration: The material after the neutralization reaction is sent to a plate and frame filter press and filtered at a pressure of 0.6 MPa to obtain a filtrate.
[0110] (4) Modulation: The filtrate was cooled to room temperature and the concentration was adjusted to 9.0 wt % (Al2O3 content) to obtain the final product.
[0111] The obtained low-aluminum polyaluminum chloride product has the following characteristics: Al2O3 content 9.0% by weight, basicity 35%, pH value (1% solution) 4.0, relative density (20°C) 1.20.
[0112] Compared with Example 4, the coagulation effect of the product prepared in Comparative Example 4 is significantly poorer, and the treatment efficiency is only 60-70% of that of Example 4 under the same conditions; the coagulation activity of the product is greatly reduced under low temperature conditions; the product has poor treatment effect on water bodies with high chroma and high organic matter content.
[0113] In this comparative example, the fluorine-containing hydrochloric acid was not pretreated and was directly used to prepare solid polyaluminium chloride.
[0114] Specifically, the preparation process of Comparative Example 5 includes the following steps: (1) Polymerization reaction: 120.0 parts by weight of 33.0% by weight fluorine-containing hydrochloric acid (fluorine content 2500 ppm) was directly added to the reaction kettle, stirring was started, and the speed was adjusted to 200 rpm. 34.0 parts by weight of aluminum hydroxide were added twice. The temperature was raised to 95° C. and the reaction was carried out at this temperature for 4.0 hours to obtain a reactant.
[0115] (2) Neutralization reaction: The reactants were transferred to a neutralization kettle, 7.5 parts by weight of calcium aluminate powder was added, and the mixture was reacted at 90° C. for 1.0 hour.
[0116] (3) Filtration: The material after neutralization reaction is sent to a plate and frame filter press for filtration to obtain a filtrate.
[0117] (4) Spray drying: After adjusting the concentration of the filtrate, spray drying is performed directly to obtain a solid product.
[0118] (5) Packaging: Solid products should be simply packaged.
[0119] The obtained solid polyaluminium chloride product has the following characteristics: Al2O3 content 29.0% by weight, fluorine content about 1800 ppm, insoluble matter content 0.8% by weight, and water content 5.5% by weight.
[0120] Compared with Example 6, the product prepared in Comparative Example 5 has a high fluoride content and does not meet the requirements for drinking water treatment; fluoride volatilizes during the storage process of the product, causing secondary pollution to the environment; white precipitates are produced after the product is dissolved, affecting the use effect; the presence of fluoride ions also affects the coagulation performance and stability of the product.
[0121] By comparing the above comparative examples with the embodiments of the present invention, it can be seen that the technical measures adopted by the present invention, such as step-by-step feeding, synergistic additives, neutralization reaction optimization, waste gas treatment and heat energy recovery, enable the product to have significant performance advantages, including better coagulation effect, higher stability, wider range of application and better environmental performance, which fully demonstrates the creativity and practicality of the technical solution of the present invention.
[0122] In order to fully evaluate the advantages of the preparation process of the present invention, we conducted systematic performance testing and analysis on the products of the embodiments and comparative examples. The test methods and result analysis are described in detail below.
[0123] 1. Test Method 1. Coagulation effect test Test method: Jar-test Instruments and equipment: Six-link electric stirrer (ZR4-6, Shanghai Meiying Experimental Instrument Co., Ltd.), standard 2L beaker Test water sample: high turbidity water sample (turbidity 500±20NTU, pH 7.5±0.2, water temperature 25±1℃), prepared by kaolin Steps: Take 1000mL of water sample in a beaker; Add the polyaluminium chloride product to be tested (measured as 10mg / L according to Al2O3); Stir rapidly (200 rpm) for 1 minute; Stir slowly (40 rpm) for 10 minutes; Let it settle for 30 minutes; The supernatant was taken to measure the turbidity (using HACH 2100Q turbidimeter); Calculation method: Removal rate (%) = (original turbidity - turbidity after treatment) / original turbidity × 100% 2. Low temperature adaptability test Test method: Same as coagulation effect test, but the water sample temperature is controlled at 5±1℃; 3. Product stability test Test method: Liquid products: Place the product in an opaque sealed container and store it at room temperature (25±2℃). Take samples regularly (0, 1, 3, 6 months) to measure the Al2O3 content, pH value and coagulation effect. Solid products: Place the product in a closed environment (relative humidity 60±5%) and measure the moisture absorption rate and solubility changes at different times (0, 7, 15, and 30 days); 4. Product solubility test (solid product) Test method: Take 100mL of 25℃ deionized water in a 500mL beaker; Add 1.0 g of solid product; Under stirring conditions of 300 rpm, record the time required for the product to completely dissolve; After dissolution, the solution turbidity and insoluble matter content were measured; 5. Fluorine content test; Test method: Ion selective electrode method (GB / T 7484-1987) Instruments: fluoride ion selective electrode, pH / ion meter (METTLER TOLEDO SevenCompact S220); Steps: Prepare total ionic strength adjustment buffer (TISAB); Prepare a fluoride ion standard solution (0.1-10 mg / L) and draw a calibration curve; Sample pretreatment: Solid samples need to be dissolved and the pH adjusted to 5-6; Take 10 mL of sample and add 10 mL of TISAB solution and mix well; Immerse in fluoride ion electrode to determine content; 6. Resource consumption and environmental impact assessment Test method: Energy consumption measurement: record the energy consumption of electricity, steam, etc. for each process unit output; Wastewater generation: Determine the wastewater generation and main pollutant indicators of each process unit output; Waste gas treatment efficiency: measure the acid mist and dust concentrations before and after treatment, and calculate the removal rate.
[0124] 2. Test Results Table 1: Comparison of coagulation effects (under normal temperature 25°C)
[0125]
[0126] Note: Normal temperature efficiency ratio = low temperature removal rate / normal temperature removal rate × 100%
[0127]
[0128]
[0129] Note: Coagulation effect retention rate = removal rate after a certain period of storage / initial removal rate × 100%
[0130]
[0131]
[0132] Note: The drinking water standard refers to GB 5749-2006 "Sanitary Standard for Drinking Water", and the fluoride limit is 1.0 mg / L
[0133]
[0134] 3. Test results analysis 1. Analysis of coagulation effect As shown in Table 1, the coagulation effect of the product of the embodiment of the present invention is significantly better than that of the comparative product. The turbidity removal rate of the product of the embodiment is above 99.2%, while the removal rate of the comparative product is between 96-98%. It is particularly noteworthy that the floc formation speed of the product of the embodiment is faster (1.0-1.8min) and the floc settling speed is higher (2.5-3.5cm / min), which is of great significance for the filter load and effluent water quality in actual water treatment projects.
[0135] Example 3 (solid product) and Example 2 (concentrated polyaluminium chloride) exhibited the best coagulation effect, which was mainly attributed to the combined effects of the batch feeding technology, neutralization reaction optimization and addition of synergists of the present invention, which enabled the product to have a more reasonable aluminium polymer distribution structure.
[0136] 2. Low temperature adaptability analysis The data in Table 2 show that the product of the embodiment of the present invention still maintains a relatively high treatment efficiency under low temperature conditions, with the removal rate maintained between 98.6-99.0%, and the retention rate reaches 99.2-99.7% compared with the efficiency under normal temperature conditions. However, the treatment efficiency of the comparative product decreases significantly under low temperature conditions, with the removal rate being only 84.9-92.3%, which is 6.8-11.9 percentage points lower than that under normal temperature.
[0137] Example 4 (low-aluminum high-efficiency product) shows the best low-temperature adaptability (normal temperature efficiency ratio 99.7%), which is mainly due to the synergistic effect of activators such as iron salts, manganese salts and copper salts added therein. These metal ions still maintain high hydrolysis activity under low temperature conditions, making up for the deficiency of the decreased hydrolysis rate of aluminum ions at low temperatures.
[0138] 3. Product stability analysis As can be seen from Table 3, the liquid product of the embodiment of the present invention still maintains good stability after long-term storage (6 months), the Al2O3 content changes little (-0.5 to -1.0%), the coagulation effect retention rate is high (92.5-96.5%), and the amount of sediment generated is small (1.0-1.8%). In contrast, the Al2O3 content of the comparative product decreases significantly (-4.2 to -5.8%) after storage over the same period, the coagulation effect is greatly reduced (retention rate is only 45.2-58.2%), and a large amount of sediment is generated (15.4-22.6%).
[0139] Example 2 (concentrated polyaluminium chloride) exhibits the best storage stability, which is due to the composite stabilizer and structure regulator added in the present invention, which can effectively prevent further polymerization and precipitation of the aluminium polymer and maintain the long-term stability of the product.
[0140] 4. Solid product performance analysis The data in Table 4 show that the solid product of the embodiment of the present invention has excellent solubility (dissolution time 2.5-2.8min) and low insoluble content (0.25-0.35%), and low hygroscopicity (30-day moisture absorption rate is only 2.8-3.2%). The solid product of the comparative example has a long dissolution time (7.5-9.8min), a high insoluble content (0.85-1.15%), and strong hygroscopicity (30-day moisture absorption rate reaches 12.8-15.4%).
[0141] The solid product of Example 3 performed best, which was mainly attributed to the combined effect of the spray drying process optimization, the application of the two-fluid nozzle and the addition of nano-silicon dioxide as a fluidity improver of the present invention, which made the product have a more uniform particle size distribution and better physical properties.
[0142] 5. Fluoride content and drinking water application assessment Table 5 shows that the fluorine content of the products of the embodiments of the present invention is significantly lower than that of the products of the comparative examples, especially the fluorine content of the embodiment 6 (fluorine-free product) is only 45 ppm, which is much lower than 1800 ppm of the comparative example 5. This makes the products of the present invention more suitable for drinking water treatment, and the residual fluorine content in the treated water can meet the drinking water standard requirements.
[0143] Example 6 performed best, which was due to the raw material deep pretreatment technology of the present invention. By adding calcium oxide for pre-precipitation, the fluorine content in the hydrochloric acid was significantly reduced, thereby obtaining a high-quality product suitable for drinking water treatment.
[0144] 6. Resource consumption and environmental impact analysis The data in Table 6 show that, although the energy consumption and steam consumption of the process of the embodiment of the present invention are slightly different from those of the comparative example, it has significant advantages in terms of wastewater generation, waste gas treatment efficiency and pollutant emissions. The wastewater generation of the process of the embodiment is reduced by 33-40%, the waste gas treatment efficiency is increased by 7.5-14.8 percentage points, and the COD and fluoride emissions are reduced by 58-86% and 93-96%, respectively.
[0145] This is mainly due to the comprehensive application of the thermal energy cascade utilization, wastewater recycling and efficient waste gas treatment system of the present invention, which not only improves the resource utilization efficiency but also significantly reduces the environmental impact.
[0146] 4. Conclusion Through the above system testing and analysis, it is fully proved that the polyaluminium chloride preparation process of the present invention has the following significant advantages over the traditional process: Excellent coagulation effect: high turbidity removal rate, fast floc formation, fast sedimentation rate, and treatment efficiency increased by 2-3 percentage points; Strong low temperature adaptability: It can still maintain more than 97% of normal temperature efficiency at 5℃, which is 10-15 percentage points higher than traditional products; Good product stability: high performance retention rate after long-term storage, less sedimentation and long service life; Solid products have outstanding performance: fast dissolution, less insoluble matter, low hygroscopicity, and easy to use; Excellent environmental protection indicators: low fluoride content, the water quality after treatment meets the drinking water standards, and the equipment is less corrosive; Significant resource conservation: reduced wastewater generation, high waste gas treatment efficiency, and significantly reduced pollutant emissions.
[0147] These test results fully demonstrate that the process of the present invention has successfully solved the deficiencies of traditional polyaluminium chloride products in coagulation effect, stability, adaptability and environmental protection through the comprehensive application of a series of innovative technical measures. It has significant technological advancement and practical value, and provides an efficient, stable and environmentally friendly polyaluminium chloride preparation process for the water treatment field.
[0148] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing polyaluminium chloride, characterized in that: The following steps are involved: (1) Polymerization reaction: 100.0-120.0 parts by weight of 31.0-33.0 wt % hydrochloric acid is added to a reaction kettle, stirring is started, 30.0-35.0 parts by weight of aluminum hydroxide is added in batches at a speed of 200-250 rpm under a slight negative pressure of -50 Pa to -100 Pa, heating is stopped after heating to 70±2° C., and the reaction is kept at 90-100° C. for 3.0-4.0 hours to obtain a first-step material; (2) Neutralization reaction: the first-stage material is transferred into a neutralization kettle, and under a slight negative pressure of -50 Pa to -100 Pa, the calcium aluminate powder is added in a ratio of 100.0 parts by weight of the first-stage material to 5.0-8.0 parts by weight of the calcium aluminate powder in 3-5 times, each time interval is 5-8 minutes, the stirring speed is 180-220 rpm, and the reaction is carried out at 85-95° C. for 0.5-0.8 hours; (3) filter pressing: adding 0.2-0.5 parts by weight of diatomaceous earth and 0.01-0.03 parts by weight of polyacrylamide to the material after the neutralization reaction, and then filter pressing at a pressure of 0.6-0.8 MPa to obtain a filtrate; (4) Modulation: The filtrate is cooled through a graphite heat exchanger, and the concentration is adjusted and corresponding additives are added according to the product type to obtain a polyaluminium chloride product.
2. The preparation process according to claim 1, characterized in that: In the step (1), the aluminum hydroxide is added in batches as follows: first add 20% of the total amount, react for 5-10 minutes, then add 30% of the total amount, and then react for 10-15 minutes before adding 50% of the total amount; the aluminum hydroxide content is ≥99.0% by weight, and the fineness is 100-200 mesh.
3. The preparation process according to claim 1, characterized in that: In the step (2), 0.05-0.1 parts by weight of alkaline phosphate and 0.2-0.5 parts by weight of MgSO4·7H2O are further added; the CaO·Al2O3 content in the calcium aluminate powder is 65.0-75.0% by weight, and the fineness is 200 mesh-325 mesh.
4. The preparation process according to claim 1, characterized in that: The modulation step further comprises: (a) when preparing dilute polyaluminium chloride, the concentration of the filtrate is adjusted to 10.0±0.2 wt %, and 0.1-0.2 wt % of trisodium citrate, 0.05-0.1 wt % of modified polyacrylic acid and 0.01-0.02 wt % of MnCl2·4H2O are added; or (b) When preparing concentrated polyaluminium chloride, the concentration of the filtrate is adjusted to 12.5±0.3 wt %, and 0.1-0.2 parts by weight of a composite stabilizer is added.
5. The preparation process according to claim 1, characterized in that: The process also includes a raw material pretreatment step: adding 0.1-0.2 parts by weight of H2O2 to the hydrochloric acid for pretreatment; in step (1), 0.1-0.3 parts by weight of FeCl3·6H2O are also added; in step (2), 0.2-0.4 parts by weight of Al2(SO4)3·18H2O are also added.
6. The preparation process according to claim 1, characterized in that: The process also includes a waste gas treatment step: the waste gas generated in the process is discharged after being subjected to two-stage water spray absorption and one-stage alkali solution spray absorption in sequence; wherein the pH value of the water spray is 6-7 and 7-8 respectively, and the pH value of the alkali solution spray is 10-11; the waste gas treatment adopts a mixed filler of polypropylene ball ring and ceramic Raschig ring, the filling density is 120-150kg / m³, the height of the filler layer is 1.2-1.5m / layer, and the swirl plate and the filler are arranged alternately.
7. A process for preparing solid polyaluminium chloride, characterized in that: The following steps are involved: (1) preparing concentrated polyaluminium chloride having a concentration of 12.5±0.3 wt % according to any one of claims 1 to 6; (2) Spray drying: preheat the concentrated polyaluminium chloride to 60-70°C, transport it to the spray drying buffer tank through a spray drying feed pump, and spray dry it under hot air at 320-350°C using a dual-fluid nozzle (gas-liquid ratio 2:1-3:1), with the outlet temperature controlled at 90-110°C and the negative pressure in the tower at -0.001 MPa, to obtain solid polyaluminium chloride; (3) Packaging: The solid polyaluminium chloride is transported to the packaging equipment via an auger conveyor for packaging, and the packaging specification is 25±0.2 kg / bag.
8. The preparation process according to claim 7, characterized in that: In the step (2), 0.1-0.3 parts by weight of nano-silicon dioxide is added to the concentrated polyaluminium chloride as a fluidity improver; the Al2O3 content of the obtained solid polyaluminium chloride is ≥28.0% by weight, the insoluble matter content is ≤0.5% by weight, and the moisture content is ≤5.0% by weight.
9. The preparation process according to claim 7, characterized in that: In the step (3), a polyethylene plastic bag with a thickness of 0.08-0.10 mm is used as the inner layer and a polypropylene woven bag is used as the outer layer for packaging, and 3-5 g of desiccant is added into the packaging bag.
10. The preparation process according to claim 7, characterized in that: The waste gas generated during the spray drying process is discharged through a 25m high exhaust stack after passing through a first-level cyclone dust removal, a first-level semi-finished product solution spray, a first-level water spray and a first-level alkali solution spray in sequence; the process also includes a recycling step: the hot gas (90-110°C) discharged from the spray drying is used to preheat the neutralization reaction feed, and the waste gas washing water is partially reused in the production of dilute polyaluminium chloride.
Citation Information
Patent Citations
Method for preparing high-basicity high-concentration polymeric aluminum
CN106186020A
Preparation method of polyaluminium chloride for polyaluminium chloride flocculating agent
CN112110465A
Friedel-Crafts reaction aluminum-containing wastewater resource utilization method
CN114133058A
Preparation process of high-performance polyaluminum chloride flocculant
CN114804311A
Preparation method of scaling-free polyaluminum chloride
CN115947362A